Synthesis and characterisation of thermomesogenic polysiloxanes with 2,5-dihydropyrrolo[3,4-c]pyrrole-1,4-dione units in the main chain - Horn, M; Hepuzer, Y; Yagci, Y; Bilgin-Eran, B; Cernenco, U; Harabagiu, V; Pinteala, M; Simionescu, BC (PERGAMON-ELSEVIER SCIENCE LTD, 2002)
The synthesis of the first two liquid crystalline polysiloxanes bearing 3,6-diaryl-2,5-dihydropyrrolo-[3,4-c]pyrrole-1,4-dione units in their main chain are described. Investigations on their thermotropic phase behaviour by polarising microscopy reveal nematic or smectic enantiotropic phases, respectively. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: polysiloxanes; liquid crystals; diketopyrrolopyrrole; FUNCTIONAL POLYSILOXANES; POLYMERS; DPP; Polymer Science